Study on the performance of the ordinary portland cement as soil stabilizing agent for silty soils / A. Ibrahim ...[et al.] - Ibrahim, A.; Abdullah, J.; Hamid, A.H.A; Ahmad, A. (2006)
The infrastructure development in Malaysia has grown impressively and construction projects are carried out almost everywhere although at the not very suitable sites, which sometimes consist of problematic fine soils. According to Mutallib (1991), there are about 65% of soil in Malaysia consisting affine soil such as clay, silt, peat and organic Soil, where 8% (2.6 million hectares) is covered with peat and organic soil. Thus, the researchers and engineers job in stabilizing Gild Improving the quality of soft soil is vital 10 ensure the safety and economic of the design and construction projects. There are many methods available for improving soil quality and one of them is by mixing stabilizer agents with the soils, which may be natural soil, industrial by products or waste material, and cementations and other chemicals. The study focuses on the effectiveness and performances of the ordinary Portland cement (OPC) as a soil stabilization agent on the fine soil. Stabilization is done jar combination of soil-cement mixtures with cement content at 1.5 and 10% by weight of dry soil and with curing periods of 0, 1 and 7 days. The basis jar comparing the various proportions of stabilizer is the value of California Bearing Ratio. The result shows the strength characteristics of stabilized soil in terms of CBR exhibited a significant increase compared to the untreated samples. The addition of 1%, 5% and 10% of OPC provides stronger material for road sub-base and base course. The highest improvement jar cement stabilization is 1420% which is obtained by the addition of 10% cement using 7 days curing time compared to the untreated soils. In terms of CBR value, the performance is 102.3 % where the highest value obtained is 13.5kN compared to the standard CBR value, which is 13.2kN The result shows that there was a significant increase in strength in terms of CBR value for stabilized soil compared to the untreated samples.